Analysis of Emission Reduction in Indonesia's Power Generation Sector for the Centennial Milestone using Grammatical Evolution and ARIMA - Raharjo, Jangkung; Wijayanto, Inung; Nur Ikhsan, Rifki Rahman; Indra Wijaya, Igpo; Nugroho, Bambang Setia; Rokhmat, Mamat (Society of Visual Informatics, 2025)
This study examines the Indonesian government's commitment to reducing electricity production, a crucial element in achieving sustainable energy. Historically, Indonesia depends on non-renewable energy sources, including coal and oil. Indonesia is presently transitioning to cleaner energy alternatives. This policy is done to align with the objective of global sustainability. This pivotal action by the Indonesian government aims to accelerate the adoption of low-carbon technology by society. Through careful planning, Indonesia aims to establish a sustainable and resilient energy framework that addresses both current and future environmental challenges. The active participation of both the state and private sectors is crucial to support this transition. For instance, investment in research and development of sustainable technology by the private sector can accelerate the improvement or creation of a more sustainable energy framework. Innovative technologies, such as solar, hydropower, and wind, can significantly contribute to reducing carbon footprints. This study conducted an extensive observation and evaluation of the contribution of Indonesia's power generation sector to achieving net-zero emissions. This study utilizes the Autoregressive Integrated Moving Average (ARIMA) and Grammatical Evolution (GE) to predict the overall electrical capacity trajectory leading up to Indonesia's Centennial in 2045. By utilizing the exponential grammar, GE outperforms ARIMA in predicting energy forecasts. This research sheds light on Indonesia's transformative efforts, contributing to a broader understanding of how to cultivate a sustainable and environmentally responsible energy future.